Technical Papers and Discussions - Ore Reduction and Slags - An Electrochemical Study of the Properties of Molten Slags of the System CaO-SiO2 and CaO-Al2O3-SiO2 (Metals Tech., Oct. 1946, T. P. 2101, with discussion) - G. Derge (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1948)
The chemical and physical propertties of slag systems are of special interest to metallurgists, for nearly all metals are in contact with molten slags during the primary reduction from their ores and then during the subsequent refining and alloying processes that determine their ultimate use. These processes are carried out at high temperatures and involve such complex chemical systems that funda-mental scientific knowledge of the Properties and behavior of these slags is inadequate. Various hypotheses have been Proposed to explain known slag characteristics. The commonest of these regard the molten slag as constituted of compounds that are dissociated in varying degrees into their constituent oxides, as illustrated by Schenckl and the recent Papers of Chipman and co-authors. Another proposal is that these compounds dissociate by com-plete6 or partial ionization, the evidence for which has been reviewed by Martin and Derge.? whatever hypothesis is favored, the exact formulation of these compounds is incomplete. It is based on three principal types of information: 1. Studies of solidified 51% samples by X ray diffraction, petrography, and similar methods that can be used at room temperature. The correlation of this information with the high-temperature properties of the molten slag is uncertain. 2. Studies of slag-metal equilibria, which have the advantage of providing observations on the molten slag at high temperature. However, even these data present problems of interpretation because they require a complete knowledge of the metal phase. 3. Direct measurements of properties of molten slag at the temperature of greatest metallurgical interest. Viscosity, electrical conductivity, specific heats, and similar properties have been measured, but the data of this type are widely scattered and frequently difficult to interpret. Additional direct measurements of properties of molten slag that can be interpreted in terms of chemical behavior are required, and this paper shows that the standard physical-chemical measurement of reversible electrode potentials, which measure the activity of specific constituents, is a fruitful source of such information. The purpose of this investigation, therefore, was to find an electrode combination that would yield reversible electromotive force measurements when dipped into the molten slag to be studied. Slags of the systems cao-sio2 and cao-120,-SiO2 were chosen for study because graphite containers could be used and the data could be correlated with those for viscosity, conductivity, and other proper-